2012
DOI: 10.1590/s1020-49892012001000003
|View full text |Cite
|
Sign up to set email alerts
|

Conocimientos, percepciones y comportamientos relacionados con el consumo de sal, la salud y el etiquetado nutricional en Argentina, Costa Rica y Ecuador

Abstract: There is public awareness about salt, but not about the term "sodium." More salt and sodium are consumed than what is reported and there are no prospects of reducing that consumption. Although it is understood that excessive consumption of salt is a health risk, participants do not perceive that they are at risk. Replacing the word "sodium" with the word "salt" would facilitate food selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 10 publications
1
25
0
11
Order By: Relevance
“…The HBM provides an explanatory framework to understand why some individuals in these communities intend to prevent triatomine infestation and others do not. Relevant to the specific context, the HBM has been used successfully across Latin America and, specifically, in Ecuador [11,[17][18][19], and its constructs are translatable and applicable to Spanish-speaking populations [20,21]. The HBM argues that there are five antecedents to behavior change [22,23].…”
Section: The Health Belief Modelmentioning
confidence: 99%
“…The HBM provides an explanatory framework to understand why some individuals in these communities intend to prevent triatomine infestation and others do not. Relevant to the specific context, the HBM has been used successfully across Latin America and, specifically, in Ecuador [11,[17][18][19], and its constructs are translatable and applicable to Spanish-speaking populations [20,21]. The HBM argues that there are five antecedents to behavior change [22,23].…”
Section: The Health Belief Modelmentioning
confidence: 99%
“…Estudios recientes en América Latina reportan consumos elevados de sodio, junto con el desconocimiento de la población sobre los efectos de dicho mineral sobre la salud (18).…”
Section: Discussionunclassified
“…A statement relating to the presence of sodium in salt was not encountered in the findings of the project study. A research carried out by Sánchez et al (2012) in Argentina, Costa Rica and Ecuador revealed that those people who do not know the definition of salt are not aware of what the sodium in salt is. The fact that there were no opinions on the presence of sodium in this study can be related to the fact that the number of the students defining salt was low.…”
Section: Discussionmentioning
confidence: 99%
“…That the subject is dealt with in three different disciplines in different ways might result in a terminology problem relating to salt. Sánchez et al (2012) showed the fact that there is not a common terminology as the reason of not comprehending the concept of salt and emphasized that a terminology should be created. The terms that are present in the teaching of salt should be reduced to a level that students can understand.…”
Section: Discussionmentioning
confidence: 99%